Handbook of GC-MS : Fundamentals and Applications. - Hübschmann, Hans-Joachim (Wiley, 2015)
The only comprehensive reference on this popular and rapidly developing technique provides a detailed overview, ranging from fundamentals to applications, including a section on the evaluation of GC-MS analyses. As such, it covers all aspects, including the theory and principles, as well as a broad range of real-life examples taken from laboratories in environmental, food, pharmaceutical and clinical analysis. It also features a glossary of approximately 300 terms and a substance index that facilitates finding a specific application. For this new edition the work has been now extended to two.